Pengaruh jarak transportasi terhadap biokimia darah ayam broiler - Bagus Aji Purwadi; Teysar Adi Sarjana; Retno Murwani (Faculty of Animal Science, Universitas Brawijaya, 2018)
The objective of this research is to examine the effect of transportation distance on haemoglobin, hematocrit, erythrocytes, plasmaglucose, triglyceride and cholesterol of broilers. Two hundred and fifty two broilers with an average body weight of 2.0 ± 0.08 kg were dividedinto transportation distance namely T1: 60 km, T2: 120 km, T3: 180 km. The data were analyzed by Anova whenthere was a significant effect Duncan test was conducted. Longer transportation distance significantly decreased plasma hemoglobin, hematocrit and triglyceride (P≤0,05), while erythrocytes, glucose and cholesterol level were not significantly affected (P>0.05).The conclusion of this study is broiler transport at a distance of 120 km has reduced hemoglobin, hematocrit, and plasma triglyceride levels.